Kualiti kehidupan penjaga kepada kanak-kanak berpenyakit asma di Hospital Universiti Sains Malaysia (HUSM) - Maria Farrah, Wahid (PPSP, Universiti Sains Malaysia, 2007)
Asthma is a chronic inflammatory disease that contributed highly morbidity among pediatric. Asthma disease burden not only affect the children but also their caregiver's quality of life especially their parent. The objective is to measure pediatric asthma caregiver's quality of life that includes emotional function and activity daily living. This is descriptive research with cross-sectional design and had been done to pediatric asthma caregiver. Data were collected using distributed research question to 48 pediatric asthma caregiver which had treatment in HUSM. Data were analyzed by using descriptive, independent sample-t test and analysis of varians (ANOVA). Result of the study showing that pediatric asthma caregiver's quality of life is at moderate level. Emotional function of 79.2% caregiver is at moderate concern. While activity limitation for majority of the caregiver is also at moderate limitation. There is no significant different between demographic factors of the pediatric asthma caregiver and their quality of life (p>0.05}. In conclusion, pediatric asthma affects quality of life of their caregiver at the moderate level. So, researcher hope that health care professional will concern about this issue and play their role in helping caregiver especially the parent in managing their child asthma. Proper asthma managing could less asthma morbidity and will increase their caregiver's quality of life to the great level.